الرضا الوظيفي لدى معلمات رياض الأطفال في محافظتي اللاذقية وطرطوس (Latakia University Journal - Arts and Humanities Sciences Series, 2013)
يهدف البحث الحالي إلى التعرف على درجة الرضا الوظيفي لمعلمات رياض الأطفال في محافظتي اللاذقية وطرطوس، وتعرَف الفروق في مستوى الرضا تبعاً للمتغيرات الآتية (تابعية الروضة، الحالة الاجتماعية، عدد سنوات الخبرة، المستوى التعليمي). استخدم البحث المنهج الوصفي التحليلي، واشتملت العينة على (180) معلمة من معلمات رياض أطفال المحافظتين للعام الدراسي 2012/2013. ولتحقيق هدف البحث صممت استبانة مكونة من أربعة محاور، احتوت (62) فقرة، تمثل الرضا الوظيفي لمعلمات رياض الأطفال. أظهرت النتائج أن معلمة رياض الأطفال راضية عند محور العناية بالأطفال، في حين أنها راضية إلى حد ما عند المحاور الآتية (العلاقة مع أولياء الأمور والمجتمع المحلي، الراتب والأمور المالية في الروضة، طبيعة العمل في الروضة)، وبينت النتائج وجود فروق دالة في درجة الرضا الوظيفي تبعاً لمتغير تابعية الروضة لصالح الرياض العامة، ووجود فروق دالة تبعاً لمتغير الحالة الاجتماعية لصالح المعلمات العازبات، وكذلك وجود فروق دالة تبعاً لمتغير عدد سنوات الخبرة لصالح ذوي الخبرة أقل من 5 سنوات، كما أن الفروق الدالة تبعاً لمتغير المستوى التعليمي جاء لصالح حملة الثانوية والمعهد المتوسط. وقدم البحث عدة مقترحات منها: تحسين الراتب لمعلمات رياض الأطفال ليكون كافياً لهن في تأمين الأمور الحياتية. The research has aimed at recognizing the degree of functional satisfaction for kindergarten teacher women in Tartous and Lattakia governorates. It has also aimed at recognition of differences in the level of satisfaction according to four variables. The research has used the descriptive and analytical method and the specimen has included (180) teacher women of the kindergartens in two governorates. In order to achieve its aims the research has used a questionnaire of four axis and (62) parties representing the functional satisfaction of kindergarten teacher women. The results have indicated that teacher women are satisfied with looking after children, where as they are somewhat satisfied with three axis the results have also shown significant difference in the degree of functional satisfaction according to the variable of the relation attachment- connection of the kindergarten in favor of the public kindergartens, it has also been shown significant differences according to the variable of the social status in favor of single teacher women. There have also been significant difference according to the variable of experience in favor of experienced with less than five years. so, there have been significant difference according to the variable of educational level in favor of teachers with secondary certificates and intermediate institute. finally the research has offered many suggestion